2011
DOI: 10.1016/j.neulet.2010.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, neuropathological, and neuroimaging characteristics of early-onset Alzheimer's disease due to a novel PSEN1 mutation

Abstract: Background-Familial Alzheimer's disease (AD) due to PSEN1 mutations provides an opportunity to examine AD biomarkers in persons in whom the diagnosis is certain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
3
31
1
Order By: Relevance
“…Hallucinations and delusions were reported more frequently in PSEN1 A79V MCs from this family, as has been noted previously in individuals with ADAD. 44,45 These findings demonstrate that the clinical phenotypes of late-onset ADAD and LOAD can overlap, and suggest that previously reported clinical (e.g., seizures, early myoclonus, spastic paraparesis, dysarthria, and rapid decline [9][10][11][12][13][14][15][16][17][18] ) and neuropathological differences (e.g., altered cerebral Aβ 42 and neurofibrillary tangle deposition, increased prevalence of cerebral amyloid angiopathy, and formation of "cotton wool" plaques 6,12,16,[19][20][21][22][23][24][25][26][27] ) may reflect age-or mutation-dependent effects.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Hallucinations and delusions were reported more frequently in PSEN1 A79V MCs from this family, as has been noted previously in individuals with ADAD. 44,45 These findings demonstrate that the clinical phenotypes of late-onset ADAD and LOAD can overlap, and suggest that previously reported clinical (e.g., seizures, early myoclonus, spastic paraparesis, dysarthria, and rapid decline [9][10][11][12][13][14][15][16][17][18] ) and neuropathological differences (e.g., altered cerebral Aβ 42 and neurofibrillary tangle deposition, increased prevalence of cerebral amyloid angiopathy, and formation of "cotton wool" plaques 6,12,16,[19][20][21][22][23][24][25][26][27] ) may reflect age-or mutation-dependent effects.…”
Section: Discussionsupporting
confidence: 63%
“…7,8 Also, ADAD may be characterized by clinical features that are unusual in LOAD, including pyramidal signs, hypo/hyperkinetic movement disorders, ataxia, and early myoclonus and seizures. [9][10][11][12][13][14][15][16][17][18] Additional differences in the pattern of cerebral Aβ 42 deposition are reported in some ADAD cases, including 6,16,19,20 higher Aβ 42 burden and greater densities of neurofibrillary tangles; [21][22][23] increased Aβ 42 deposition within the cerebellum [24][25][26] and basal ganglia; 19,20 ; and higher prevalence of cerebral amyloid angiopathy and large diffuse so-called "cotton wool" plaques. 12,22,24,27 Such clinical and pathological differences may challenge whether findings from studies of early-onset ADAD, including current trials of anti-amyloid therapies, 28 can be extrapolated to the understanding of the far more common LOAD.…”
Section: Introductionmentioning
confidence: 99%
“…In both symptomatic and presymptomatic APP , PSEN1 and PSEN2 mutation carriers, the majority of the studies found a decrease in Aβ 42 and an increase in both t-tau and p-tau levels when compared with healthy control individuals, consistent with a typical AD profile [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] (table 1). In some cases, 1 or more markers were found to be unchanged compared to controls [27,28,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The neuropathological changes in FAD are generally similar to those in sporadic AD,3 but atypical neuropathology has been reported in some cases, including the presence of ‘cotton wool’ plaques in the cerebral cortex, non-neuritic amyloid plaques in the cerebellum and degeneration of corticospinal tracts and the basal ganglia 3 5 6. In-vivo neuroimaging studies of FAD mutation carriers show reduced temporal lobe and hippocampal volumes before the onset of symptoms 7.…”
Section: Introductionmentioning
confidence: 82%
“…Analyses of these subjects’ MRI scans have previously been published 6 10 25. High-resolution T1-weighted three-dimensional (3D) images were acquired in the sagittal plane using an MPRAGE sequence (TR=1900 ms, TE=4.38 ms, TI=1100 ms, flip angle 15°, voxel size 1×1×1 mm 3 ).…”
Section: Methodsmentioning
confidence: 99%